Czarownica w literaturze polskiego oświecenia. Stereotyp i płeć - Kowalewska, Danuta (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The article focuses on the image of witches in the iconography, literature, and imagination of the inhabitants of Early Modern Europe (from the late Middle Ages to the Enlightenment). It endeavours to explain whether the role and function of magical figures in Early Modern literature is conditioned by gender and by the conviction that magic is related to the biological functions of women. I will also attempt to determine how the stereotype of the witch emerged and whether its function in literaturę was influenced by the changed relations between the sexes in the 18th century. Although the main area of interest are works in Polish, numerous references to foreign literature are also made.